Towards a Spiritual Experience Level: A Need Assessment of the Hajj and Umrah’s Pilgrims in KBIHU Al-Falah Malang - Ramadhan, Mochammad Rizal; Hasanah, Samudra Mutiara; Khoirunnisa, Tsania (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: The spiritual experience that pilgrims have before Hajj and Umrah pray is an important role of the implementation of ritual. Spiritual experience has not been a commonly researched topic at this time. A preliminary study in the form of a needs analysis is a crucial first step in identifying and knowing the level of spiritual experience. This study aims to describe the level of experience of Hajj and Umrah’s pilgrims at KBIHU Al-Falah. The method used in this research is quantitative survey with instruments that have been assessed as valid through adaptation of a previous instrument. Data from the analysis of spiritual experience needs for Hajj and Umrah pilgrims at KBIHU Al-Falah Malang (n = 30 participants) showed 33,33% have high spiritual experience, 56,67% have moderate spiritual experience, and 10% have low spiritual experience. This study provides preliminary evidence that pilgrims need a qualified spiritual experience before Hajj and Umrah.